PERAN STRATEGI COPING TERHADAP KECEMASAN MASA DEPAN PADA FRESH GRADUATE - Gusneli, Nasya Pitri; Pratama, Mario (STKIP Pesisir Selatan, 2025)
This study aims to examine the role of coping strategies in future anxiety among fresh graduates who are undergoing the transition from higher education to the workforce. A competitive labor market and increasing unemployment rates among university graduates may contribute to heightened future anxiety in this population. This study employed a quantitative approach using purposive sampling. The participants consisted of 289 fresh graduates who had completed their studies within the last 0–2 years. Data were collected using the Dark Future Scale to measure future anxiety and a coping strategies scale based on Carver’s framework, which includes problem-focused coping, emotion-focused coping, and less useful coping. Data analysis was conducted using multiple linear regression with SPSS version 26.0. The results indicated that coping strategies, both simultaneously and partially, did not have a significant role in predicting future anxiety among fresh graduates. These findings suggest that future anxiety is more strongly influenced by external and structural factors rather than individual coping mechanisms. This study provides empirical evidence that enriches the literature on post-graduation psychological dynamics and offers a foundation for future research to explore other relevant predictors of future.